Insights into Job Satisfaction in the Sugar Industry: Wawasan tentang Kepuasan Kerja di Industri Gula - Oktafian , Rio; Komala Sari, Dewi (Indonesian Journal of Innovation Studies, 2024)
This study investigates the impact of organizational commitment, job characteristics, and career development on employee job satisfaction in PT. PG Candi Baru, a sugar company in Sidoarjo, Indonesia. Using quantitative research with 130 permanent employees, data was collected via Likert scale questionnaires and analyzed using path analysis techniques with SmartPLS software. The results confirm that organizational commitment, job characteristics, and career development positively influence employee job satisfaction. These findings underscore the importance of fostering organizational commitment, improving job characteristics, and providing career development opportunities to enhance overall employee satisfaction and organizational performance in the sugar industry. Highlight: Quantitative Analysis: Path analysis with SmartPLS software for robust statistical insights. Positive Relationships: Organizational commitment, job characteristics, career development enhance satisfaction. Industry Relevance: Vital implications for enhancing satisfaction in the sugar industry. Keywoard: Organizational Commitment, Job Characteristics, Career Development, Employee Job Satisfaction, Sugar Industry